Are measures of voice hearing distinct from measures of emotional states, recovery and well-being? A factor analysis study - Sofia Loizou; Andy P. Field; David Fowler; Mark Hayward (PLoS ONE, 2025)
Background Conceptually, there may be some overlap between measures of voice hearing experiences and measures assessing broader outcome domains. Despite this possibility, it is unknown whether measures of voice hearing and broader outcomes are assessing similar or separate concepts. This study aimed to examine whether measures of voice hearing are distinct from measures of emotional states, well-being and recovery. Methods Study 1 examined whether the Hamilton Program for Schizophrenia Voices Questionnaire is distinct from the Depression Anxiety Stress Scale-21 and the Short Warwick-Edinburgh Mental Well-being Scale using secondary data (n = 401). Study 2 examined whether the Psychotic Symptoms Rating Scale for Auditory Hallucinations is distinct from the Hospital Anxiety Depression Scale and the CHoice of Outcome in Cbt for psychoses short form using baseline data from two randomized controlled trials (n = 187). Results In Study 1, a six-factor model was found to be reasonable and accounted for 54.04% of the total variance (F1: 13%, F2: 11.26%, F3: 8.55%, F4: 4.04%, F5: 7.30%, F6: 9.9%). In Study 2, a five-factor model was identified and accounted for 39.99% of the total variance (F1: 15.52%, F2: 7.47%, F3: 6.53%, F4: 6.70%, F5: 3.78%). Within both studies, the items from the voice hearing measures loaded uniquely onto factors that contained no items from other measures. Conclusion Findings show that measures of voice hearing are distinct from broad outcome measures and therefore are measuring separate concepts. This confirms the psychometric properties of the voice hearing measures and provides some clarity around outcomes and their measurement.